Dividend Policy as a Moderating Variable on the Relationship between Profitability, Leverage and Firm Value in the Consumer Goods Manufacturing Sector Listed the Indonesia Stock Exchange - Kurniawanto, Hudi; Widarno, Bambang; Hapsari, Yogandhini Maharani (Archives of Business Research, 2025)
This study aims to analyze the effect of profitability and leverage on company value with dividend policy as a moderating variable. The population in the study is the Consumer Sector Manufacturing Companies Listed on the IDX in the period 2020-2022. The data source of this study is secondary data. The analysis method of this study uses Descriptive Statistics, Classical Assumption Test, Hypothesis Test, Multiple Linear Regression Analysis, Moderated Linear Regression Test (MRA). The results of the study indicate that profitability and leverage have a significant effect on firm value. While profitability and leverage with dividend policy as a moderating variable have a significant effect on firm value.